The antecedents of knowledge sharing among human resource fraternity in oil and gas company / Siti Nor Ain Fatiah Mohamed Hanafiah - Mohamed Hanafiah, Siti Nor Ain Fatiah (2016)
Knowledge sharing has been important role in organizations nowadays. Performance of the organization is credited to knowledge and information. Intellectual capital is considered to be the most important assets. But dilemma is that only some organization focus on generation and preservation of knowledge. The purpose of this research is that we want to find out about the relationship between the knowledge sharing and the variables that are organizational citizenship behavior (OCB), trust and participative decision making (PDM). Every organization needs the knowledge sharing in order to gain any new ideas and to spread the knowledge among the people in that organizations. In order to share the knowledge with others, it might be difficult if we do not have a good relationship with them. The relationship must be built through the certain way. The result of the findings for this research is that the variables that were used are positive and significant towards the knowledge sharing. The result is not also important to the employees but also to the leaders. Data was collected through questionnaire from Human Resources (HR) fraternity in PETRONAS KLCC using convenience sampling technique. Sample size was 173 and 138 complete questionnaires were received back. Results of this research are significant and prove that the OCB, trust and PDM are bigger influence in organization.